2005
DOI: 10.1002/pssb.200510032
|View full text |Cite
|
Sign up to set email alerts
|

Antiferro–ferromagnetic transformation in LaMnO3 under neutron irradiation

Abstract: It is known (see, e.g., the review [1]), that the dielectric LaMnO 3 of stoichiometric composition has an O′-type orthorhombic structure formed with the participation of both the tilting modes (ϕ, ψ ) and the Jahn-Teller (JT) mode Q 2 [2]. Measurements of the magnetic susceptibility of LaMnO 3 show preferably positive exchange interaction between Mn 3+ ions, but at low temperatures this oxide behaves as an A-type antiferromagnet [1]. The main role in formation of this type of antiferromagnetism is played by J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The radiation induced defects and vacancies were believed to generate ferromagnetism in the above materials. Interestingly, it is also shown that neutron and electron irradiation can be employed in manipulating the magnetic properties of magnetically active materials such as LaMnO3 (antiferromagnetism to ferromagnetism) and La0.9Ca0.1CoO3 (increase in magnetization) 7,21 . These changes were attributed to ion displacements and lattice expansion.…”
mentioning
confidence: 99%
“…The radiation induced defects and vacancies were believed to generate ferromagnetism in the above materials. Interestingly, it is also shown that neutron and electron irradiation can be employed in manipulating the magnetic properties of magnetically active materials such as LaMnO3 (antiferromagnetism to ferromagnetism) and La0.9Ca0.1CoO3 (increase in magnetization) 7,21 . These changes were attributed to ion displacements and lattice expansion.…”
mentioning
confidence: 99%